Loss of RBBP4 results in defective inner cell mass, severe apoptosis, hyperacetylated histones and preimplantation lethality in mice. Issue 1 (14th April 2020) - Miao, Xiaosu; Sun, Tieqi; Barletta, Holly; Mager, Jesse; Cui, Wei
Abstract: Retinoblastoma-binding protein 4 (RBBP4) (also known as chromatin-remodeling factor RBAP48) is an evolutionarily conserved protein that has been involved in various biological processes. Although a variety of functions have been attributed to RBBP4 in vitro, mammalian RBBP4 has not been studied in vivo . Here we report that RBBP4 is essential during early mouse embryo development. Although Rbbp4 mutant embryos exhibit normal morphology at E3.5 blastocyst stage, they cannot be recovered at E7.5 early post-gastrulation stage, suggesting an implantation failure. Outgrowth (OG) assays reveal that mutant blastocysts cannot hatch from the zona or can hatch but then arrest without further development. We find that while there is no change in proliferation or levels of reactive oxygen species, both apoptosis and histone acetylation are significantly increased in mutant blastocysts. Analysis of lineage specification reveals that while the trophoblast is properly specified, both epiblast and primitive endoderm lineages are compromised with severe reductions in cell number and/or specification. In summary, these findings demonstrate the essential role of RBBP4 during early mammalian embryogenesis. Abstract : RBBP4 is essential during early embryo development in vivo, loss of RBBP4 results in defective inner cell mass (ICM), severe DNA damage and apoptosis, hyperacetylated histones and preimplantation lethality in mice.